2017
DOI: 10.21815/jde.016.027
|View full text |Cite
|
Sign up to set email alerts
|

Annual ADEA Survey of Dental School Seniors: 2016 Graduating Class

Abstract: This report examines the results of the American Dental Education Association (ADEA) Survey of Dental School Seniors graduating in 2016. Data were collected from 4,558 respondents at all 59 U.S. dental schools with graduating classes that year. This annual survey asks graduating students about a variety of topics in order to understand their motivation for attending dental school, educational experiences while in school, debt incurred, and plans following graduation. Motivations for choosing to attend dental s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
56
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 42 publications
(61 citation statements)
references
References 6 publications
5
56
0
Order By: Relevance
“…In regards to asking respondents about barriers for new dentists, student loan debt was the number one reason provided by all respondents as the primary barrier for new dentists to become part time clinical adjunct faculty members. The annual ADEA survey of dental school seniors, found that graduates have an average student loan debt ranging from $129,639 to $223,984 for the classes of 2005–2015 (ranging from $0 to $550,000) [11]. Increased student debt translates into longer payment durations and balancing educational debt and living expenses.…”
Section: Discussionmentioning
confidence: 99%
“…In regards to asking respondents about barriers for new dentists, student loan debt was the number one reason provided by all respondents as the primary barrier for new dentists to become part time clinical adjunct faculty members. The annual ADEA survey of dental school seniors, found that graduates have an average student loan debt ranging from $129,639 to $223,984 for the classes of 2005–2015 (ranging from $0 to $550,000) [11]. Increased student debt translates into longer payment durations and balancing educational debt and living expenses.…”
Section: Discussionmentioning
confidence: 99%
“…11 In fact, 39% of those faculty members were between 60 and 70 or greater years of age, meaning that over the next ten years or so there will be a significant number of retiring faculty members who will need to be replaced. 13 The 2007-08 ADA dental faculty report showed that, of the 56 dental schools then in operation, over half (n=31) shared their basic science faculty members with their institution's medical school. For both those years, half (51%) of new faculty members came from private practice, and 15% to 18% were graduates of advanced education programs.…”
Section: Tenure Status and Agementioning
confidence: 99%
“…6,7 Therefore, incorporating implant training into predoctoral curricula and establishing competency criteria to assess training are becoming critical. 9,10 Challenges identified in establishing implant instruction in predoctoral dental education are cost for implementation, limited funding, patient availability, and limited time in the curriculum. 8 However, in annual surveys of dental school seniors over the past several years, implant dentistry has been one of top areas in which students perceived that the time spent in the curriculum was inadequate.…”
mentioning
confidence: 99%